BUSINESS COMPETITION IN IMPLEMENTATION GOVERNMENT TENDER - Albert Ben Affendy; Arbina Florenchia; Dinda Evita; Ella Lirpa Simaremare (Universitas Muhammadiyah Ponorogo, 2020)
The Business Competition Supervisory Commission (KPPU) has the authority to examine and decide on alleged violations of business competition in tenders under Law No. 5 of 1999 concerning Prohibition of Monopolistic Practices. The results of the study of Case Verdict Number: 34 / KPPU-L / 2009 are that there are several facts that business actors have violated Article 22 of Law Number 5 of 1999 that fulfills elements of conspiracy, the form of conspiracy is vertical collusion and conspiracy horizontal. In Case Decision Number 34 / KPPU-L / 2009 it is shown that a violation of business competition has Elements that can determine that there is an unfair business practice, in this case it is stated that Reported I, Reported II, Reported III, Reported IV, Reported V, Reported VI was proven to have been legally and convinced to have carried out a tender conspiracy. The formulation of the problem in the research is an analysis of the authority of the KPPU and the elements of a tender conspiracy. The type of research that was used in this journal were the Normative Research Type, and the data collection technique used is the literature study